First World War Commemorations in Belgium and the Netherlands: comparative perspectives - Wellings, Ben (BMGN - Low Countries Historical Review, 2016)
Memory of the First World War is refracted through that of other conflicts. Although these are the first ‘global’ commemorations, national narratives and politics loom large. Commemoration is still dominated by national framing. If the role of war commemoration is to create an affective link between state and citizen, then on the evidence of contestation derived from Belgium, the Netherlands and beyond, we may conclude that it operates more at an individual, local and national level than a consciously European or global one.This article is part of the forum 'Commemorating War 100 years after the First World War'.